The Influence of Personal Selling and Service Quality on Jenius Application User Satisfaction and Loyalty Using the E-Servqual Model - Fidya Nur Styaningsih; Abidin, Zaenal (Journal of Advances in Information Systems and Technology, 2025)
This study examines the influence of personal selling and service quality in the Jenius app on user satisfaction and loyalty in Indonesia, in the context of increasing internet usage reaching 78.19% by 2023. Bank BTPN, through the Jenius app, capitalizes on technological developments to provide secure and efficient mobile banking services. Although the Jenius app is growing in popularity, various complaints related to bugs, OTP code issues, login difficulties, and transaction barriers have emerged, which may affect user satisfaction and loyalty. This study uses a quantitative method with the E-ServQual framework and Cognition Affective Behavior (CAB) theory to analyze data from 301 Jenius user respondents, which were collected through an online questionnaire using purposive sampling technique. The data was analyzed using partial least squares-structural equation model (PLS-SEM) with the help of SmartPLS 4. Of the nine hypotheses proposed, seven hypotheses were declared significant (accepted). So it can be concluded that the factors that influence the satisfaction and loyalty of Jenius application users are service quality (SQ) which consists of efficiency (EF), fulfillment (FUL), and system availability (SA). In addition, personal selling (PS) only directly affects user satisfaction (SAT), and user satisfaction affects loyalty (LO). Based on the accepted hypothesis, the research shows that application service quality and personal selling have a direct influence on Jenius application user satisfaction. However, user loyalty is only influenced by service quality, and not by personal selling.